Experiences of Physical and Psychological Violence Against Male Victims in Canada: A Qualitative Study - Dim, Eugene Emeka (International journal of offender therapy and comparative criminology, 2021)
The concept of intimate partner violence (IPV) implies gender-neutrality in the experiences of violence. Gender symmetry in IPV implies similar numbers of men and women victims. Data from the 2014 Canadian General Social Survey (Victimization) indicate that 262,267 men and 159,829 women were victims of self-reported spousal violence over the past 5 years. Despite the prevailing notion that IPV predominantly affects female victims, these data suggest that men too are victims of IPV, especially in heterosexual relationships. However, very few qualitative studies have shed light on heterosexual male victims’ experiences of IPV. This article describes some of these experiences and also seeks to understand the effects of IPV on male victims. Qualitative data collected through semi-structured interviews with 16 male victims of IPV were used to explore their experience of physical IPV and psychological IPV, as well as the consequences of such abuse. Results revealed common themes pertaining to the type of abuses (i.e., physical, controlling and threatening behaviours, and verbal abuse) male victims experienced and the subsequent physical and psychological impacts. This study identifies the need to distinguish between physically and psychologically abused male victims of IPV.